(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Since the US intervention, the international Coalition has been implementing Post-Modern measures and policies in Afghanistan. Nevertheless Afghanistan is not a Modern but a Pre-Modern State. The reason for the adoption of inaccurate policiesis the need for all the members of the coalition to account on the approval oftheir public opinions.